Remoção de íons sulfato aplicando a hidrocalumita calcinada como agente precipitante - Santana, Dantara Freires (2020)
The hydrocalumite (Ca2Al(OH)6Cl.2H2O), a layered double hydroxide (LDH), was synthesized and calcined at different temperatures in order to evaluate its application as a precipitating agent in the sulfate removal. For the characterization of the used mate